Methylation of Eugenol Using Dimethyl Carbonate and Bentonite as Catalyst - Dina Asnawati; I Made Sudarma; Emmy Yuanita; Baiq Fadila Arlina; Saprini Hamdiani; Siti Raudhatul Kamali (Universitas Gadjah Mada, 2015)
Eugenol is a compound with a variety of reactive functional groups such as allyl, hydroxy and methoxy. The presence of the functional groups brings eugenol possible to undertake the transformation into various derivative compounds with diverse activities. One of the simple and possible transformations is methylation or alkylation. Commonly, methyl halides and dimethyl sulphate are used as methylation agent. However, those kinds of methylation agents are toxic and carcinogenic. In this research dimethyl carbonate, an alternative methylation agent is used, because of its low toxicity, green, and economic. The synthesis has been carried out by using a catalyst. Bentonite was activated by heating to a temperature using 300 °C. Methylation was shown by the formation of a light yellow liquid (25.71% yield). The structures of products were characterized by GC-MS and obtained a compound, namely bis eugenol (4-allyl-2-methoxyphenoxy) methane (2.37% yield).